Biotic homogenisation in bird communities leads to large‐scale changes in species associations. Issue 3 (14th December 2021) - Rigal, Stanislas; Devictor, Vincent; Gaüzère, Pierre; Kéfi, Sonia; Forsman, Jukka T.; Kajanus, Mira H.; Mönkkönen, Mikko; Dakos, Vasilis
Abstract : The impact of global change on biodiversity is commonly assessed in terms of changes in species distributions, community richness and community composition. Whether and how much associations between species are also changing is much less documented. In this study, we quantify changes in large‐scale patterns of species associations in bird communities in relation to changes in species composition. We use network approaches to build three community‐aggregated indices reflecting complementary aspects of species association networks. We characterise the spatio–temporal dynamics of these indices using a large‐scale and high‐resolution dataset of bird co‐abundances of 109 species monitored for 17 years (2001–2017) from 1969 sites across France. We finally test whether spatial and temporal changes in species association networks are related to species homogenisation estimated as the spatio–temporal dynamics of species turnover (β‐diversity) and community generalism (community generalisation index). The consistency of these relationships is tested across three main habitats, namely woodland, grassland and human settlements. We document a directional change in association‐based indices in response to modifications in species turnover and community generalism in space and time. Weaker associations and sparser networks were related to lower spatial species turnover and higher community generalism, suggesting an overlooked aspect of biotic homogenisation affecting species associations and may also have an impact on species interactions. We report that this overall pattern is not constant across habitats, with opposite relationships between biotic homogenisation and change in species association networks in urban versus forest communities suggesting distinct homogenisation processes. Although species associations contain only partial signatures of species interactions, our study highlights that biotic homogenisation translates to finer changes in community structure by affecting the number, strength and type of species associations.